PENATAAN KAWASAN OBJEK WISATA ALAM DODOKU AER KONDE DESA WAWALI KECAMATAN RATAHAN - Walansendow, Agustinus; Kamumu, Nardiansyah; Kadamehang, Gerry; Pangkarego, Lidia S. (Jurnal Ilmu Pariwisata, 2023)
Tourism has a very important influence and role in the development of a region. Southeast Minahasa Regency is an area that has a diversity of tourist attractions. The Dodoku Aer Konde natural tourist area is one of the superior tourist areas, with its attraction and beauty found in the clarity of the water and the cool and cool air. However, this tourist area still lacks attention, complete facilities are not available, some facilities are starting to break down, and the layout is not good. The research with the title "Arrangement of the Dodoku Aer Konde Natural Tourist Attraction Area, Wawali Village, Ratahan District, Southeast Minahasa Regency" has a problem formulation, namely how to arrange and complete the tourism facilities and infrastructure in the Dodoku Aer Konde Natural Tourist Attraction area. This research aims to describe and explain the arrangements that will be carried out and identify the completeness of tourism facilities and infrastructure in the Dodoku Aer Konde Nature Tourism area. This research uses a qualitative descriptive research method. The data sources used in this research are primary data obtained through direct observation at the research location including land use patterns, physical condition of the land, accommodation, condition of facilities and infrastructure and vegetation as well as secondary data in the form of notes obtained from interviews with the government or village communities. , including population, topography and location maps. Data collection was carried out by literature review, observation, documentation and interviews. Based on the research results, it was concluded that the Dodoku Aer Konde natural tourist area needs to be reorganized and repaired damaged facilities as well as the provision of incomplete facilities and infrastructure. Arrangements, improvements and procurement of facilities are carried out in order to support tourism progress and increase the attractiveness of the Dodoku Aer Konde natural tourist area.